The Effect of Work Culture, Discipline, and Morale on Employee Performance - Triastuti, Desy; Cahyani, Rusnandari Retno; Kusumastuti, Anggit Dyah (Journal of Educational Management Research, 2025)
This study aims to examine the effects of work culture, discipline, and work enthusiasm on employee performance, with a specific focus on Generation Z employees at the Office of Trade and Cooperatives for Small and Medium Enterprises in Wonogiri Regency. Using a quantitative approach, a sample of 155 respondents was selected from a population of 224 employees through convenience sampling based on the Slovin formula. Data were collected using both online and offline questionnaires and analyzed with SPSS version 27. The findings show that work culture does not have a significant impact on employee performance. In contrast, both work discipline and enthusiasm have a significant and positive effect on performance. When examined simultaneously, all three variables influence performance, although only discipline and enthusiasm are individually significant. These results underscore the importance of fostering employee discipline and morale to enhance overall performance.